Analisis Kualitas Website Institut XYZ Menggunakan Metode Webqual dan IPA - Saputra, Jeki; Satrianansyah, S; Wijaya, Harma Oktafia Lingga; Rahman, Taufik (STIKOM Tunas Bangsa Pematangsiantar, 2021)
A good website is a website that is in great demand by users and provides good information to its users. One of the website applications that can be seen is in universities. To measure the quality of the XYZ Institute website, indicators that affect the quality of the website are needed from the point of view of educators, lecturers and students. Therefore, the methods used to measure the quality of the XYZ Institute website are the Webqual and IPA methods. The description of this research is whether there is an effect of the quality of the XYZ Institute website on usability indicators. Is there an effect of the quality of the XYZ Institute website on the indicators of information quality (Information Quality, is there an effect of the quality of the XYZ Institute website on the indicators of service interaction quality), and, is there an effect of the quality of the XYZ Institute website on the overall indicators. Is there an influence on the quality of the XYZ Institute website with a comparison the level of importance and level of performance in the IPA method. There is a significant influence between usability, quality information and service interaction quality on user satisfaction both partially and simultaneously. In the IPA method in developing the Institute website XYZLubuklinggan In quadrant I has an important priority where the indicators in quadrant I are indicators X16 and X17 and this quadrant is not in accordance with user expectations and has a high level of importance. In Quadrant II the XYZha Institute website rus maintains the indicators are X4, X8, X10, X12, X14, X16, X18, in quadrant III can ignore a little of importance the indicators are X1, X2, X3, X5, X11, X15, and quadrant IV are considered to have a low level of importance but the level of performance on this website is considered very good for users whose indicators are X6 and X7.